2013
DOI: 10.1177/1744259113498473
|View full text |Cite
|
Sign up to set email alerts
|

Practical correlation for thermal resistance of horizontal enclosed airspaces with downward heat flow for building applications

Abstract: The 2009 ASHRAE Handbook of Fundamentals (Chapter 26) provides a table that contains the thermal resistances (R-values) of enclosed airspaces for different values of airspace thickness, effective emittance, mean airspace temperature, and temperature differences across the airspace. This table is extensively used by modellers, architects and building designers in the design for thermal resistance of building enclosures. The effect of the airspace aspect ratio (length/thickness) on the R-value is not accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 12 publications
3
42
0
Order By: Relevance
“…Unlike the R-values provided in ASHRAE table (2017), the results of those studies showed that the aspect ratios of the enclosed airspaces can have significant effects on their R-values (Saber, 2013a(Saber, , 2013b(Saber, , 2013c(Saber, , 2014a(Saber, , 2014b. In some of the studies (Saber, 2013a(Saber, , 2013b(Saber, , 2013c(Saber, , 2014a(Saber, , 2014b, considerations were given to investigate the potential increase in the R-value of the enclosed airspace when a thin sheet having different values of emissivity on both sides was placed in the middle of the airspace as shown in Figure 4(b). As will be shown later, the results showed that, depending on the value of the effective emittance, thickness of the airspace, orientation of the airspace, and direction of heat flow, the R-value could be easily doubled and in some cases could be tripled by incorporating this thin sheet along the middle of the enclosed airspace.…”
Section: Overview Of Thermal Performance Of Enclosed Spacesmentioning
confidence: 86%
See 4 more Smart Citations
“…Unlike the R-values provided in ASHRAE table (2017), the results of those studies showed that the aspect ratios of the enclosed airspaces can have significant effects on their R-values (Saber, 2013a(Saber, , 2013b(Saber, , 2013c(Saber, , 2014a(Saber, , 2014b. In some of the studies (Saber, 2013a(Saber, , 2013b(Saber, , 2013c(Saber, , 2014a(Saber, , 2014b, considerations were given to investigate the potential increase in the R-value of the enclosed airspace when a thin sheet having different values of emissivity on both sides was placed in the middle of the airspace as shown in Figure 4(b). As will be shown later, the results showed that, depending on the value of the effective emittance, thickness of the airspace, orientation of the airspace, and direction of heat flow, the R-value could be easily doubled and in some cases could be tripled by incorporating this thin sheet along the middle of the enclosed airspace.…”
Section: Overview Of Thermal Performance Of Enclosed Spacesmentioning
confidence: 86%
“…In previous studies (Saber, 2013a(Saber, , 2013b(Saber, , 2013c(Saber, , 2014a(Saber, , 2014b, the results showed that the R-value could be doubled due to installing a thin sheet in the middle of (a) low-sloped enclosed airspaces (u = 30°) with downward heat flow (Saber, 2014b), (b) high-sloped enclosed airspaces (u = 45°) with downward heat flow (Saber, 2013b), (c) vertical enclosed airspace (u = 90°; Saber, 2013a), and (d) horizontal enclosed airspace (u = 0°) with downward heat flow (Saber, 2014a). However, the R-value could be tripled if a thin sheet is installed horizontally in the middle of the horizontal enclosed airspace (u = 0°) with upward heat flow condition (Saber, 2013c).…”
Section: Effect Of Installing Thin Sheet In the Middle Of Enclosed Spacementioning
confidence: 95%
See 3 more Smart Citations